2009
DOI: 10.4067/s0034-98872009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Morbid obesity in an adolescent with Prader-Willi syndrome

Abstract: Prader-Willi syndrome is an uncommon multisystem genetic disorder caused by defects of chromosome 15 (15q11-q13)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
2
0
2
Order By: Relevance
“…The clinical characteristics of this syndrome reported in the literature, such as: neonatal hypotonia, difficulties in feeding, lethargy weak cry, hyporeflexia, hyperphagia, and obesity [7,11,15], were confirmed by the patient's mother during anamnesis. Short stature, small hands and feet, skin/hair/retina hypopigmentation, thin lips, labial commissures facing down, myopia, and strabismus also described in prior studies were also observed [4,13,14].…”
Section: Discussionsupporting
confidence: 55%
“…The clinical characteristics of this syndrome reported in the literature, such as: neonatal hypotonia, difficulties in feeding, lethargy weak cry, hyporeflexia, hyperphagia, and obesity [7,11,15], were confirmed by the patient's mother during anamnesis. Short stature, small hands and feet, skin/hair/retina hypopigmentation, thin lips, labial commissures facing down, myopia, and strabismus also described in prior studies were also observed [4,13,14].…”
Section: Discussionsupporting
confidence: 55%
“…One article described a patient with stage 3 CKD (75). Five cases were found describing acute kidney injury (76-80) due to several different causes: pneumoperitoneum with abdominal compartment syndrome (76), secondary rhabdomyolysis caused by hyperpyrexia (77), nephrotoxic medication (78), hyperosmolar hyperglycemic state (79) and respiratory failure due to obesity hypoventilation syndrome (80). We found two case reports describing adults with PWS who needed hemodialysis due to end stage kidney disease, one patient from intrinsic nephrotic disease, the other case from uncontrolled diabetes mellitus (81,82).…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Expectedly, sUA was associated with metabolic health and, in PWS, triglycerides emerged as a metabolic predictor of sUA at the multivariable regression analysis. Literature pertaining to sUA regulation in PWS is poor and restricted to case reports [35,36] and a preliminary study in obese adults with PWS, where sUA level was lower than control subjects with obesity [20]. In the general population, metabolic health and, particularly, triglycerides are recognized to play a modulatory role on sUA in relation to the cardiovascular risk [37][38][39].…”
Section: Discussionmentioning
confidence: 99%